PERSPEKTIF MODERNISASI MENUJU TERWUJUDNYA KELUARGA SEJAHTERA - Rosita Carolina (Universitas Negeri Medan, 2017)
The role of families in the establishment of science and technology is divided into two, namely as the perpetrators of change and change agents. As perpetrators of change, families must master the science and technology (IPTEK) and try to have a superior personality such as never give up, creative, disciplined, responsible, trustworthy and become the main and main educator in the family. The next benefit is that families are able to use information about science and technology and how to apply it in the life of their family members, so as to improve their lives independently to a professional family. This participation should not always be in the form of work, in the sense of devoting themselves to institutions outside the household or the like, but more than that is working in the sense of carrying out its duties as a giver of life in the household. The family in its capacity as a whole personality developer is thorough, need to perform and prevent the negative impact of modernization of science and technology in the global dimension. For the realization of this role, the family must be able to prepare family members can withstand the mental shocks due to the influence of global science and technology. This is the subject of further trends, the meaning of modernization and its influence on the family as one of the center of attention today.